2017
DOI: 10.32964/tj16.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Paper coated with sonochemically synthesized zinc oxide nanoparticles: Enhancement of properties for preservation of documents

Abstract: Sonochemically synthesized zinc oxide (ZnO) nanoparticles were coated on paper for enhancing its properties in view of the preservation of documents. The paper used for accession register was used as substrate. Physical, chemical, optical, hydrophobic, and antifungal properties of the coated and uncoated papers were compared. Nanoparticles were synthesized with ultrasound from organic precursors and were characterized by X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM), whereas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…pH is one measure of paper’s stability, as it indicates the degradation of α-cellulose and affects the printing of paper. There is a standard requirement of neutral pH (7.0) for writing and printing papers (BISIS:1848, 2007) [ 30 ]. The results indicated that the PBA coating did not cause any immediate alteration of pH on the paper samples, statistically.…”
Section: Resultsmentioning
confidence: 99%
“…pH is one measure of paper’s stability, as it indicates the degradation of α-cellulose and affects the printing of paper. There is a standard requirement of neutral pH (7.0) for writing and printing papers (BISIS:1848, 2007) [ 30 ]. The results indicated that the PBA coating did not cause any immediate alteration of pH on the paper samples, statistically.…”
Section: Resultsmentioning
confidence: 99%
“…According to the results from ultrasonic treatments, in particular by the probe device, it is important to highlight the smaller structures obtained with a high degree of porosity since these cavities can serve as nanomaterials with a high surface reactivity, applied in antibacterial [84], photo remediation of heavy metals [85], inhibition of corrosion [86] or paper preservation [87].…”
Section: Ultrasonic Treatments -Tem Characterizationsmentioning
confidence: 99%